Influence variables of ultrasound-derived fat fraction in liver fat content measurement: preprandial and postprandial states. - Cheng, Shuai; Lv, Wenhao; You, Tingjing; Zhang, Shengmin (Abdominal Radiology, 2025)
Purpose: To investigate whether there is any effect of preprandial and postprandial states of patients on Ultrasound-derived fat fraction(UDFF) in liver fat content measurement. Methods: A retrospective study was conducted on 1596 patients who underwent UDFF from January to September 2024; UDFF measurements were performed by a sonographer, who repeated each measurement 5 times before and after meals, respectively, and finally expressed them as the mean; then paired t-tests and analyses of variance (ANOVA) were used to compare the differences in preprandial and postprandial UDFF and Auto p-SWE(Auto point shear wave elastography) values among groups, and linear regression was used to analyze the differences in preprandial and postprandial UDFF and Auto p-SWE values between each group. Results: The study enrolled 1036 patients(491 males and 545 females), aged 18–89 years, mean age (56.50 ± 14.67) years. The differences in UDFF and Auto p-SWE values between the group eating protein and fatty foods (n = 613) and the group eating light foods (n = 423) were not statistically significant (p > 0.05); the differences in UDFF and Auto p-SWE values between the group with a body mass index(BMI) < 25 kg/m2 (n = 703) and the group with a BMI ≥ 25 kg/m2 (n = 333) were statistically significant (p < 0.05). Preprandial and postprandiall UDFF and Auto p-SWE values were highly positively correlated in the eating group, the protein and greasy food group, and the light food group (r = 0.985, 0.983, 0.988, r = 0.834, 0.849, 0.810, all p < 0.001). Conclusions: UDFF has good consistency in the measurement of liver fat content in preprandial and postprandial states.